2022
DOI: 10.1002/dad2.12292
|View full text |Cite
|
Sign up to set email alerts
|

Digitally generated Trail Making Test data: Analysis using hidden Markov modeling

Abstract: The Trail Making Test (TMT) is a neuropsychological test used to assess cognitive dysfunction. The TMT consists of two parts: TMT‐A requires connecting numbers 1 to 25 sequentially; TMT‐B requires connecting numbers 1 to 12 and letters A to L sequentially, alternating between numbers and letters. We propose using a digitally recorded version of TMT to capture cognitive or physical functions underlying test performance. We analyzed digital versions of TMT‐A and ‐B to derive time metrics and used Bayesian hidden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…Greater time spent with the pen lifted from the iPad could be associated with additional problems, including deficits revolving around visual scanning for successive target items and/or struggling to maintain the assigned mental set for this test, i.e., to draw a line alternating between numbers and letters. The prior studies of Du et al ( 14 ) and Fellows et al ( 39 ) tend to support this supposition. In research examining participants from the Framingham Heart Study, De Anda-Duran et al ( 47 ) found that paper and pencil Trail Making Part B pen lifts was associated with subtle but statistically significant MRI gray and white matter alterations involving frontal, parietal, and temporal lobe brain regions—regions known to be involved in working memory functions [see ( 48 )].…”
Section: Discussionmentioning
confidence: 86%
See 4 more Smart Citations
“…Greater time spent with the pen lifted from the iPad could be associated with additional problems, including deficits revolving around visual scanning for successive target items and/or struggling to maintain the assigned mental set for this test, i.e., to draw a line alternating between numbers and letters. The prior studies of Du et al ( 14 ) and Fellows et al ( 39 ) tend to support this supposition. In research examining participants from the Framingham Heart Study, De Anda-Duran et al ( 47 ) found that paper and pencil Trail Making Part B pen lifts was associated with subtle but statistically significant MRI gray and white matter alterations involving frontal, parietal, and temporal lobe brain regions—regions known to be involved in working memory functions [see ( 48 )].…”
Section: Discussionmentioning
confidence: 86%
“…Second, errors that may have been made on the dTMT-B, data from the dTMT-B practice portion of the test, and data from the companion digital Trail Making-Part A test condition were not available for analysis. As reported by other researchers ( 14 , 39 ), these data need to be presented in order to obtain a fuller appreciation of the relations between FAQ-defined IADL activities and neuropsychological problems using the dTMT-B. Third, we acknowledge that the decision to create subtle and mildly impaired FAQ groups, as described above, is somewhat arbitrary and may have affected the results as reported.…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations